Optimized decentralized adaptive control of noise and vibration for periodic disturbances - An, Fengyan; Cao, Yin; Liu, Bilong (The Journal of the Acoustical Society of America, 2018)
Decentralized control has great potential to facilitate the implementations of multichannel active noise/vibration control systems. The main drawback, however, is its inherent risk of system instability. In this letter an optimized decentralized adaptive control algorithm subject to periodic disturbances is reported. The algorithm employs the scheme of a decentralized filtered-x least mean square algorithm and utilizes optimized reference filters so that the stability of the control system can be ensured. Simulation results based on a realistic vibration isolation system demonstrate that both the stability and the convergent speed could be significantly improved.